PROBLEMATIKA ANAK SEKOLAH DASAR DALAM BERKOMUNIKASI MENGGUNAKAN BAHASA INDONESIA - Deni Wardana; Putri Arianita Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The ability to communicate effectively in Indonesian should ideally begin to develop at the elementary level. However, many primary school students still struggle to express themselves fluently. This study aims to explore the underlying factors contributing to communication difficulties among students, including internal aspects such as linguistic background and external influences like teaching methods and digital media exposure. A descriptive qualitative approach was applied, involving students from grades three to six at a public school in a semi-urban area. Data were gathered through participatory observation, in-depth interviews, and document analysis. The findings reveal various challenges, including unstructured sentence construction, code-mixing with local dialects, influence from informal digital language, and a lack of supportive environments for practicing formal communication. These insights highlight the urgency of redefining pedagogical strategies and creating language-rich settings that empower children to express themselves confidently in Indonesian within appropriate contexts.